PHENOTYPIC SCREENING OF OKRA HYBRIDS AGAINST YELLOW VEIN MOSAIC DISEASE AND SHOOT AND FRUIT BORER UNDER FIELD CONDITIONS (Applied Biological Research, 2023)
The present study aimed to phenotypically screen the okra hybrids and their  parents so as to identify tolerant or resistant genetic material against yellow  vein mosaic disease (YVMD) and okra shoot and fruit borer (OSFB). The  present study included a total of 55 single cross hybrids, 16 parents, and one  hybrid check “OH-102” which were evaluated during monsoon 2019 at  three locations (Navsari, Achhalia, and Vyara) in Gujarat (India) in RBD  design. The number of plants and fruits affected in each genotype was  counted at final harvest and percent incidence calculated for YVMD and  SFB. Okra genotypes were screened to know their response on thebasis of  plant and fruit damage severity scale. Among 72 genotypes (55 hybrids + 11  lines + 5 testers), none was free from YVMD and SFB incidence. Among the  parents, ‘Arka Anamika’ and ‘Arka Abhay’, categorized as moderately  resistant to YVMD and SFB at all test locations, were identified as the most  promising donors for future breeding. Among 55 hybrids and check 22, 17, and 14 hybrids and check “OH-102” categorized as moderately resistant for  YVMD, 15, 13, 9 hybrids for Okra Shoot Borer (OSB) and 13, 15, 16 hybrids  for Okra Fruit Borer (OFB) and check “OH-102” categorized as fair resistance at Navsari, Achhalia and Vyara, respectively. The least YVMD  and OSFB incidence in hybrids showed relatively high/ average yield  performance for fruit yield per plant at all locations, so these can be used in  the further future breeding program.
Keywords: Abelmoschus esculentus; disease intensity; okra; shoot and fruit borer; yellow vein mosaic virus; yield